2022
DOI: 10.1111/pde.14891
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical severity scores correlate with the quality of life in children with psoriasis? A cross‐sectional study of Iranian pediatric patients

Abstract: Psoriasis is a chronic inflammatory disorder, involving skin, nails, and joints. 1 This relatively common dermatosis affects both adults and children, and is characterized by circumscribed erythemato-squamous papules and plaques that may affect any body region. Psoriasis has a large impact on quality of life (QoL) due to disease symptoms such as pruritus, the physical appearance of skin lesions, and complications due to treatment such as adverse drug effects and costs of treatment. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Any aspect of the work that has involved human patients has been conducted obtaining the ethical approval of all relevant bodies. Zeinab Aryanian MD 1,2 Fatemeh Ijadi MD 1 Maryam Nasimi MD 1,3 Hamidreza Mahmoudi MD 1,3 Iman Menbari Oskouie MD, MPH…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Any aspect of the work that has involved human patients has been conducted obtaining the ethical approval of all relevant bodies. Zeinab Aryanian MD 1,2 Fatemeh Ijadi MD 1 Maryam Nasimi MD 1,3 Hamidreza Mahmoudi MD 1,3 Iman Menbari Oskouie MD, MPH…”
Section: Con Clus Ionmentioning
confidence: 99%
“…[7][8][9] Many of dermatologic disorders such as psoriasis and alopecia areata have been shown to be triggered or exacerbated by even a mild psychological stress. [10][11][12][13] Perhaps, COVID-19 has been among the most stressful crises the world has confronted to; therefore, it is reasonable that those infected to the virus and those who are concerned about getting infected, experience distressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can lead to several systemic complications including cardiovascular, metabolic, and psychiatric problems. 1 , 2 , 3 Previous studies have shown some ocular manifestations in patients with psoriasis, especially those with arthropathic or pustular variants of the disease. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%